2015
DOI: 10.12669/pjms.312.6569
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of nucleotide excision repair and homologous recombination repair pathways and their role in the risk of osteosarcoma

Abstract: Objective:To evaluate the influence of polymorphisms in nucleotide excision repair (NER) and homologous recombination repair (HRR) pathways on the development of osteosarcoma patients.Methods:Genotypes of ERCC1 rs11615 and rs3212986, ERCC2 rs1799793 and rs13181, NBN rs709816 and rs1805794, RAD51 rs1801320, rs1801321 and rs12593359, and XRCC3 rs861539 were conducted by Polymerase Chain Reaction Restriction Fragment Length Polymorphism (PCR-RFLP) assay.Results:Total 148 osteosarcoma patients and 296 control subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Two studies 6 , 7 for the relationship between ERCC1 rs3212986 (8092 C>A) gene polymorphism and osteosarcoma risk were included in this meta-analysis. We found that ERCC1 rs3212986 (8092 C>A) gene polymorphism was not associated with osteosarcoma risk (A allele: OR = 0.79, 95% CI: 0.56–1.12, P = 0.18; AA genotype: OR = 0.68, 95% CI: 0.30–1.57, P = 0.37; CC genotype: OR = 1.05, 95% CI: 0.78–1.40, P = 0.76).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies 6 , 7 for the relationship between ERCC1 rs3212986 (8092 C>A) gene polymorphism and osteosarcoma risk were included in this meta-analysis. We found that ERCC1 rs3212986 (8092 C>A) gene polymorphism was not associated with osteosarcoma risk (A allele: OR = 0.79, 95% CI: 0.56–1.12, P = 0.18; AA genotype: OR = 0.68, 95% CI: 0.30–1.57, P = 0.37; CC genotype: OR = 1.05, 95% CI: 0.78–1.40, P = 0.76).…”
Section: Resultsmentioning
confidence: 99%